Дослідження системи транспортного обслуговування пасажирів за показниками якості - Никончук, В. М.; Nykonchuk, V. (ЦНТУ, 2022)
У роботі обґрунтовано параметри якості системи транспортного обслуговування пасажирів. Запропоновано комплексний показник якості для оцінки якості пасажирських перевезень, який враховує загальні критерії якості перевізного процесу та якості системи обслуговування пасажирів. На основі визначених критеріїв якості транспортного обслуговування пасажирів проведено соціологічне опитування жителів міста Рівне. Проведені дослідження дали можливість виявити слабкі та сильні сторони транспортного забезпечення, ідентифікувати ключові критерії, що визначають якість його роботи. The parameters of the quality of the passenger transport service system are substantiated in the work. To assess the quality of passenger traffic, a comprehensive quality indicator is proposed, which takes into account the general criteria of the quality of the transportation process and the quality of the passenger service system. The level of satisfaction with public transport was determined by individual criteria and in general by indicators: informing passengers; state of stops; traffic schedules; experience in using public transport; staff (conductors / drivers); fare; overall level of satisfaction with the work of transport. On the basis of the defined criteria of quality of transport service of passengers the sociological interrogation of inhabitants of the city of Exactly is carried out. According to individual criteria and indicators in general, the level of satisfaction with public transport was assessed. As the assessment of the quality of transport services is subjective, we have proposed a rating scale for respondents: from 0 to 10 (where 0 means "Very dissatisfied" and 10 - "Very satisfied"). According to the results of the survey and the calculation of the average score according to certain criteria, the variation range of answers of the city residents was distributed on a scale from 0 to 10 points. When calculating the complex quality indicator, users preferred trolleybuses with an average score of 6.3, compared to 5.6 - for minibuses. The conducted research made it possible to identify the weaknesses and strengths of transport support, to identify key criteria that determine the quality of its work. To increase the level of satisfaction with public transport and ensure the quality of transport services, a number of measures have been proposed, the implementation of which is possible with the close cooperation of representatives of education, government and business.
Research of Passenger Transport Service System by Quality Indicators
Keywords: громадський транспорт; транспортне обслуговування; критерії якості транспортного обслуговування; комплексний показник; рівень задоволеності транспортною послугою; public transport; transport service; criteria of transport service quality; complex indicator; level of satisfaction with transport service